An investigation of functional correlates and predictors of apathy in a Memory Clinic sample - Sebolai, Katlego (Department of Psychology, 2025)
Apathy is a common neuropsychiatric symptom in neurological and psychiatric illnesses and is associated with adverse outcomes, significant caregiver burden, cognitive and functional impairment, and poor quality of life. Marin's (1991) definition of apathy as an amotivational disorder has gained widespread acceptance, despite recent contentions about this conceptualization. Marin's Apathy Evaluation Scale reflects his view on apathy as constituted by motivation related deficits. In this study I used Marin's Apathy Evaluation scale to assess apathy in a sample of patients (n = 200) presenting at the University of Cape Town/Groote Schuur Hospital's memory clinic with a query of subjective cognitive impairment. I then investigated the cognitive and functional correlates of apathy in this sample. Due to recent debates on the dimensions of apathy symptoms and the disorder's diagnostic features, I initially performed an exploratory factor analysis of the Apathy Evaluation Scale to determine its factors. I then examined associations between the resulting factors or dimensions of the AES and disease-related characteristics such as depressive symptoms (measured on the Cornell Scale for Depression), year-on cognitive impairment (measured on the Deterioration Cognitive Observee), and functional impairment (measured on the Bristol Activities Daily Living Scale). I found that depression and functional impairment were significant predictors of apathy. Behavioral, cognitive, and emotional subdomains of apathy predicted decline in basic and instrumental activities of daily living differently. Lastly, year-on cognitive impairment was not a predictor of apathy. Results from the exploratory factor analysis supported a three-factor model of the Apathy Evaluation Scale but it yielded a sub-domain of social apathy instead of emotional apathy. Previous factor analysis studies reported emotional apathy, together with behavioral and cognitive apathy as sub-domains of apathy. Results from this study have important implications for understanding factors that influence patients' capacities for performing activities of daily living and meeting their functional needs.